Measurement of differential cross sections in the kinematic angular variable ϕ * for inclusive Z boson production in pp collisions at √s=8 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Nature, 2018)
Measurements of differential cross sections dσ/dφ ∗ and double-differential cross sections d2σ/dφ ∗d|y| for inclusive Z boson production are presented using the dielectron and dimuon final states. The kinematic observable φ ∗ correlates with the dilepton transverse momentum but has better resolution, and y is the dilepton rapidity. The analysis is based on data collected with the CMS experiment at a centre-of-mass energy of 8 TeV corresponding to an integrated luminosity of 19.7 fb−1 . The normalised cross section (1/σ) dσ/dφ ∗ , within the fiducial kinematic region, is measured with a precision of better than 0.5% for φ ∗ < 1. The measurements are compared to theoretical predictions and they agree, typically, within few percent.